2001
DOI: 10.1088/0953-8984/13/15/310
|View full text |Cite
|
Sign up to set email alerts
|

Optical absorption studies on the trapping states of CaS:Eu,Sm

Abstract: The optical absorption spectra of CaS:Eu,Sm at several concentrations of Eu (from 0 to 0.05 mol%) were examined to clarify the electron trapping mechanism for its photo-stimulated luminescence. Corresponding to the electron and hole trapping states, the difference between the absorption spectra after and before excitation was observed. The substructure of the infrared band of the absorption difference is eclipsed by the 4f-4f absorption of Sm3+ ions in accordance with the photo-stimulation spectrum. In compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…This can be ascribed to the trapping of excitation energy by deep traps created by Sm 3+ co-doping. [38][39][40] PL decay curves show a nearly identical PL lifetime of 0.31 ms for Eu 2+ in CaS:0.06%Eu 2+ and CaS:0.06% Eu 2+ , 0.006%Sm 3+ NCs (Fig. 2b).…”
Section: Structure and Morphologymentioning
confidence: 77%
See 2 more Smart Citations
“…This can be ascribed to the trapping of excitation energy by deep traps created by Sm 3+ co-doping. [38][39][40] PL decay curves show a nearly identical PL lifetime of 0.31 ms for Eu 2+ in CaS:0.06%Eu 2+ and CaS:0.06% Eu 2+ , 0.006%Sm 3+ NCs (Fig. 2b).…”
Section: Structure and Morphologymentioning
confidence: 77%
“…Notably, the PersL intensity and aerglow time of CaS:Eu 2+ ,Sm 3+ NCs decreased signicantly in comparison with those of CaS:Eu 2+ NCs, as a result of deep traps caused by Sm 3+ co-doping. [38][39][40] It was also found that the PersL intensity of CaS:Eu 2+ ,Sm 3+ NCs depended critically on the wavelength of the illumination light with the maximum at 470 nm (Fig. S13 †).…”
Section: Structure and Morphologymentioning
confidence: 90%
See 1 more Smart Citation
“…However, upon illumination of the material with infrared excitation, visible emission can be obtained (provided the powder has previously been excited by UV or visible light, x-rays…, which discriminates it from an up conversion phosphor). The exact defect structure caused by the introduction of the rare earth ions and its influence on the energy level scheme has not been fully established yet [211,212]. Furthermore, the phosphor’s behavior strongly depends on the concentrations of the Sm and Eu dopants [213].…”
Section: Persistent Luminescence and Storage Phosphorsmentioning
confidence: 99%
“…Their studies were rough and unreasonable because they considered only the nearestneighbor interaction and regarded it as a constant potential. Recently, based on the study of Kawamura and Do Yi-Jing, et al, and using the results obtained by Yi You-Min, et al, [7] Zhang Zhi, et al [8,9] Xie Chuan-Mei, et al [10] further studied the phase transitions of the 2D monatomic and the 2D binary systems by introducing the Lennard-Jones (L-J) potential into the 2D Collins model taking into account the existence of the empty lattice points. They not only obtained the whole phase diagram of monatomic system including the triple point and the critical point, but also obtained some simple solid-liquid phase diagrams of the 2D binary system, e.g.…”
Section: Introductionmentioning
confidence: 99%